WHAT DID INFLUENCE THE STUDENTS OF THE ELEMENTARY PRESERVICE TEACHERS' COMMITMENT? A STUDY ON THE EFFECT OF STUDENT'S SELF-LEADERSHIP AND SELF-CONCEPT - Nur Atikoh (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2022)
This study's objective was to investigate how self-leadership and self-concept influenced the students of elementary preservice teachers' commitment to the teaching profession. Students of elementary preservice teachers were employed in this study. The method was quantitative. Meanwhile, the data collection techniques consisted of questionnaires and documentation. The data analysis used descriptive statistical analysis and tested normality, homogeneity, multicollinearity, and heteroscedasticity. The hypothesis testing was used to test simple multiple regression linearity and multiple regression linearity test. As a result of the study, it has been determined that there were positive effects on the self-leadership, self-concept, and commitment of the teaching profession of elementary preservice teachers. Further investigation was required to explore that relationship. It is suggested that different self-leadership and self-concepts influenced the commitment to the teaching profession of elementary preservice teachers. Implications of the result were discussed.